Evaluation of the Color Change of the Resins During and After the Period of Validity - Marçal, Yuri Lobo Valle; Faria, George Dicarlo Rolim; Fernandes Aguiar, Frederico Nardeli; Ferraz, Laura Nobre; Baggio Aguiar, Flávio Henrique; Leite Lima, Débora Alves Nunes; Miranda, Diogo de Azevedo (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Composite resins are materials that have in their organic matrix different components that can change their initial state after the expiration date established by the manufacturer. Objective: to evaluate in vitro the possible color change of two composite resins used during and after the period of validity. For this, composite resins LLis color A1 and A2 will be selected, inside and outside the shelf life. Methods: For each resin (4 groups) were made ten discs (n = 10), of 5mm x 2mm. The analyzes were carried out in an environment with lighting and temperature controlled by a single examiner. Results: The spectrophotometric test was performed using the Vita EasyShade® device in which the values of the Vitta scale and the Cie system L * a * b * were obtained. The values of ΔE were obtained by comparing the specimens of expired and non-expired resins and showed that, regardless of the color tested, the resins did not change color. Conclusion: Regardless of the color, the resins out of the shelf life showed no color difference.